Transarterial chemoembolization combined with atezolizumab plus bevacizumab conversion therapy for intermediate-stage hepatocellular carcinoma: a case report and literature review - Ai, Haidong; Gong, Ting; Ma, Yongbiao; Ma, Guixu; Ding, Wei; Ding, Weibao; Wang, Wenjuan; Zhao, Xuelin (Frontiers in Immunology, 2024)
Hepatocellular carcinoma (HCC) ranks as the sixth most common malignancy globally, with the majority of patients presenting at the initial diagnosis with locally advanced or metastatic disease, precluding the opportunity for curative surgical intervention. With the exploration and advancement of locoregional treatments, novel molecular-targeted therapies, anti-angiogenic agents, and immunomodulatory drugs, the management of HCC has seen an increase in objective response rates and prolonged duration of response significantly enhancing the potential for conversion to resectable disease in intermediate and advanced-stage unresectable HCC. Herein, we present a case of Barcelona Clinic Liver Cancer stage B unresectable HCC, where after two courses of treatment with transarterial chemoembolization combined with atezolizumab plus bevacizumab significant tumor reduction was achieved. Per Response Evaluation Criteria in Solid Tumors 1.1, partial response culminated in successful curative surgical resection. No drug-related adverse reactions occurred during hospitalization, and there has been no recurrence during the 11-month postoperative follow-up. For patients with Barcelona Clinic Liver Cancer stage B (intermediate-stage) unresectable HCC, the transarterial chemoembolization combined with atezolizumab plus bevacizumab regimen may offer improved therapeutic outcomes leading to a higher success rate of conversion therapy and, thus, improved survival.